On fuzzy autocatalytic set - Ashaari, A. (Academic Press, 2016)
Fuzzy autocatalytic set (FACS) is one of the branch from graph theory. This FACS is used to introduce the fuzziness on connectivity of a graph. The introduction of FACS has given more accurate concept in application according a real-life problem. In this paper, some properties on fuzzy autocatalytic set of a graph theory is presented. This result give a new insight of FACS which is then expand the development of Fuzzy autocatalytic set (FACS) in the future.